The German Mittelstand: Antithesis to the Silicon Valley entrepreneurship model? - André Pahnke; Friederike Welter (Institut für Mittelstandsforschung (IfM) Bonn, 2019)
Whilst internationally, the Mittelstand in Germany is admired and many countries try to emulate it, the current debate in Germany praises the Silicon Valley model of entrepreneurship, contrasting the Mittelstand as low-growth, low-tech and non-innovative - in short: as a hindrance to Germany's economic future. We therefore ask whether the Mittelstand actually is the antithesis to the Silicon Valley entrepreneurship model. We show that Mittelstand is more than a small and medium enterprise size, identifying its distinctive features (identity of ownership and management, sense of belonging). In this regard, we also discuss the influence of historical paths and current institutional settings on the Mittelstand model. Asking to what extent the Mittelstand is distinctive, we address its diverse contributions to economy and society. We suggest that the Mittelstand is an excellent example of everyday entrepreneurship and a vibrant segment of economy which is also competitive, innovative, and growth orientated; albeit in different ways compared to Silicon Valley entrepreneurship. In concluding, we outline ideas for future research and implications for policymakers. In our view, future research and policies should stand back from dichotomies such as "Mittelstand versus Silicon Valley entrepreneurship" and acknowledge the diversity and heterogeneity of entrepreneurship.
Keywords: L26; M13; 330; Mittelstand; context; everyday entrepreneurship